Novel benzofurane carbonyl analogs of donepezil as acetylcholinesterase inhibitors - Şahin, Zafer; Biltekin, Sevde Nur; Yurttaş, Leyla; Berk, Barkın; Küçükkılınç, Tuba Tüylü; Demirayak, Şeref (Elsevier B.V., 2022)
Donepezil is the most prescribed drug for mild to moderate Alzheimer's Disease. There is not any alternative drug with this potency yet. New scaffolds bearing benzofurans and amines are being tested for good potency on acetylcholinesterase enzyme to mimic donepezil. In this study, we synthesized 22 novel compounds (2a-b, 3a-t) namely benzofuroyl-phenylpiperazines with 3 step reaction having one microwave green synthesis step at first. Compounds were tested with a modified Ellmann method on cholinesterases. Molecular modeling studies were performed on human acetylcholinesterase X-ray crystal structure complexed with donepezil (4EY7) using Maestro Schrödinger. The most active compounds were subjected to a ?-amyloid disaggregation assay. All tested compounds showed good activity (except 3n-p bearing Cl on benzofurane) on acetylcholinesterase (0.98–54 µM) and most of the compounds showed a one-digit IC50, where donepezil was 0.12 µM. The most active compounds according to IC50 values were 3t: 0.98 µM, 3s:1.07 µM, 2b:1.08 µM and 2a: 1.14 µM. Besides, compounds did not show significant activity on butyrylcholinesterase at 100 µM. Molecular modeling studies of compounds showed a good consistency (rmsd=0.45) with the binding mode and interactions of donepezil. 2b, 3 s and 3t exhibited good disaggregation potential on 1–40 ?-amyloid. Compound 3t disaggregated more than standard drug rifampicin. Cytotoxicity test results on HEK293 (at 50 µM), showed lower cytotoxicity (except for 3j-k) compared to cisplatin (46% viability). Promisingly, the most active compounds on AChE, 2a-b and 3q-t, showed the lowest cytotoxicity (64–74% viability). Consequently, we have developed potent inhibitors of AChE with close activity to donepezil. For enzyme activity; the presence of methoxy on the aromatic site, ionizable nitrogen group and a carbonyl group on/nearly to main ring (benzofurane) asserted essentially to develop more potent compounds that are equivalent to donepezil.
Keywords: Acetylcholinesterase; Alzheimer; Benzofurane; Donepezil; Enzyme